2015
DOI: 10.1590/s2317-64312015000100001440
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do uso do SpeechEasy® nos parâmetros acústicos e motores da fala de indivíduos com gagueira

Abstract: Objetivo Investigar variações nas habilidades motoras da fala em adultos com e sem gagueira, utilizando o dispositivo de alteração do feedback auditivo SpeechEasy®. Métodos Participaram 20 adultos, dez com gagueira (nove do gênero masculino e um do feminino – média 30,9 anos) e dez controles fluentes (nove do gênero masculino e um do feminino – média 25,2 anos). O estudo comparou o desempenho dos participantes em quatro tarefas: fala espontânea, diadococinesia alternada, diadococinesia sequencial e emissão de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
(37 reference statements)
2
12
1
1
Order By: Relevance
“…Therefore, the results suggest that there was a tendency to decrease the main manifestation of the disorder, which are the SLD 1,2 . These data corroborate to the results obtained from an investigation of motor skills of people who stutter under the effect of DAF 18 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, the results suggest that there was a tendency to decrease the main manifestation of the disorder, which are the SLD 1,2 . These data corroborate to the results obtained from an investigation of motor skills of people who stutter under the effect of DAF 18 .…”
Section: Resultssupporting
confidence: 90%
“…The first study used the delayed auditory feedback for people who stutter and found that the immediate effect of DAF has improved the fluency of the participants without affecting speech naturalness 18 . The other study compared the results in fluency of two groups of stutterers -one submitted only to speech therapy and another which received, associated with the therapy, the delay in auditory feedback -and found that the group which used the delay showed greater reduction of speech disruptions and higher gain in speech rate and production of information, compared to the group that did not use this device 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed positive effects in individuals with stuttering without central auditory processing (SG) alterations, because the following reductions occurred: i) the frequency score of stuttering-like disfluencies of Stuttering Severity Instrument (17) ; (ii) the amount of blocks and monosyllabic words repetitions, and (iii) the total of disfluencies of duration. These data corroborate studies which show a decrease of the disfluencies in individuals who stutter under delayed listening condition (11)(12)(18)(19)(20)(21) . This increase in fluency represents a very relevant result for individuals with stuttering, for two main reasons: i) speech is the main form of human communication and its efficiency in transferring information depends on fluency (22) , and ii) the percentage of stuttered syllables or stuttering-like disfluencies is considered a counting measure of stuttering gold standard obtained by the speech language therapist (23) .…”
Section: Discussionsupporting
confidence: 91%
“…These disfluencies are involuntary, occur at a higher frequency in relation to general population 6 and are considered the main characteristic of the disorder 7 .…”
Section: Introductionmentioning
confidence: 99%